Tales of the Mighty Code Talkers - Francis, Lee; Miner, Janet; Francis, Lee, IV; Francis, Lee, approximately 1945-2003; Alvitre, Weshoyot; Bad Hand, Kristina; Boney, Roy, Jr. (New York : Reycraft Books, 2019)
"There has been a great deal of writing the past several decades about Native American Code Talkers of World War Two. The published works have been about Navajos and the tremendous contribution they made in the Pacific campaigns of the war. What is often overlooked is the role played in both World Wars by men of other tribes. There were Cherokee, Choctaw, Comanche, Creek and other tribal representatives with their languages involved as well.
Biographies.
Keywords: Cherokee code talkers; Comic books, strips, etc; Cherokee Indians; Comic books, strips, etc; Navajo code talkers; Comic books, strips, etc; Navajo Indians; Comic books, strips, etc; Choctaw code talkers; Comic books, strips, etc; Choctaw Indians; Comic books, strips, etc; Comanche Indians; Comic books, strips, etc; Creek Indians; Comic books, strips, etc; World War, 1914-1918; Participation, Indian; Comic books, strips, etc; World War, 1939-1945 -- Participation, Indian; Comic books, strips, etc; Korean War, 1950-1953; Participation, Indian; Comic books, strips, etc; World War, 1914-1918 -- Cryptography; Comic books, strips, etc; World War, 1939-1945 -- Cryptography; Comic books, strips, etc; Korean War, 1950-1953; Cryptography; Comic books, strips, etc; Indigenous peoples; Comic books, strips, etc; United States -- Armed Forces; Indians; Comic books, strips, etc; Graphic novels; Comic books, strips, etc; Graphic novels; Comics (Graphic works)